Protocol for elucidating metabolite binding and regulation of TET2 dioxygenase - Zhang, Shuyuan; Cheng, Zhou-Li; Ye, Dan (STAR protocols, 2025)
Epigenetic enzyme activity is coupled to cellular metabolism through their reliance on metabolic cofactors and substrates. Here, we describe steps for combining biochemical assays and saturation transfer difference (STD) NMR spectroscopy to experimentally validate metabolite binding and assess the effect on TET2 activity. This protocol enables the identification of both TET2 activators and inhibitors, providing a framework for studying the interplay between metabolism and epigenetic regulation. For complete details on the use and execution of this protocol, please refer to Cheng et al.1 [Display omitted] •Instructions for the purification of highly active, tag-free human TET2CD protein•Procedures for flow cytometry-based detection of TET2 activity in vitro•Guidance on the simultaneous screening of TET2 regulatory metabolites•Steps for STD NMR-based detection of metabolite-TET2 interactions Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics. Epigenetic enzyme activity is coupled to cellular metabolism through their reliance on metabolic cofactors and substrates. Here, we describe steps for combining biochemical assays and saturation transfer difference (STD) NMR spectroscopy to experimentally validate metabolite binding and assess the effect on TET2 activity. This protocol enables the identification of both TET2 activators and inhibitors, providing a framework for studying the interplay between metabolism and epigenetic regulation.